CURBING THE FLOODING MENACE IN ZAMFARA STATE NIGERIA: A CASE STUDY OF THE GUSAU BARRAGE BREAKAGE BY - E, Obi Lawrence (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Gusau Barrage is a suitable water project which can be employed in curbing flooding menace in Zamfara State. The breakage of the Barrage resulted to a monumental flooding incidence in 2006. This breakage of the barrage was studied through visits and available documents and literature. The research targeted on how the experience of this incidence can be applied in eliminating future occurrences of flooding in the state. The research findings revealed that nonapplication of the safety devices, poor elevation of the barrage over the highlands, high intensity of rainfall and non-desiltation of the barrage sections resulted in the collapse of the barrage. The collapse of the Barrage resulted in the flooding. This research, therefore, is of the view that future flooding in Zamfara State can be effectively curbed if the barrage is well managed; its hydraulic head raised, the desilting of the river and the introduction of other uses of the water impoundment.